2011
DOI: 10.1016/j.cmet.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Glucocorticoid Receptor and Nutritional Sensor mTOR in Skeletal Muscle

Abstract: Maintenance of skeletal muscle mass relies on the dynamic balance between anabolic and catabolic processes and is important for motility, systemic energy homeostasis, and viability. We identified direct target genes of the glucocorticoid receptor (GR) in skeletal muscle, i.e., REDD1 and KLF15. As well as REDD1, KLF15 inhibits mTOR activity, but via a distinct mechanism involving BCAT2 gene activation. Moreover, KLF15 upregulates the expression of the E3 ubiquitin ligases atrogin-1 and MuRF1 genes and negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
441
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(485 citation statements)
references
References 43 publications
28
441
4
3
Order By: Relevance
“…Whether the Dmd and RyR2 genes are primary or secondary targets of GR regulation is currently unknown. However, Klf15, Ptgds, and MuRF1 are bona fide glucocorticoid-responsive target genes that are induced by activated GR (11)(12)(13)(14). Accordingly, in the absence of an intact GR signaling pathway in cardiomyocytes, the expression of these genes is significantly repressed.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the Dmd and RyR2 genes are primary or secondary targets of GR regulation is currently unknown. However, Klf15, Ptgds, and MuRF1 are bona fide glucocorticoid-responsive target genes that are induced by activated GR (11)(12)(13)(14). Accordingly, in the absence of an intact GR signaling pathway in cardiomyocytes, the expression of these genes is significantly repressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study from this same group reported no change in skeletal muscle mass (9), while Klf15 null mice developed a severe cardiac hypertrophy in response to pressure overload (6). Alternatively, Klf15 overexpression was shown to accelerate catabolism of BCAA, resulting in myotube and skeletal muscle atrophy (28). Elevated levels of Klf15 also suppressed mTOR activity in myotubes (28), a central regulator of protein synthesis shown to be .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that mRNA expression of the transcription factor Klf15 is significantly downregulated during hypertrophy, which correlated with the reduced expression of four of its IPA-predicted targets: Ehhadh, Hadha, and Hadhb (3 components of enoyl-CoA dehydrogenase, a valine and isoleucine-degrading enzymatic complex), and Acadm (a component of a leucine-degrading enzymatic complex). In addition to these genes, Bcat2, which encodes the protein that catalyzes the initial step for the degradation of all BCAAs, is also downregulated with hypertrophy and has been reported to be regulated by Klf15 in skeletal muscle (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of these GC target genes are regulated ubiquitously, others appear to be cell-type selective, suggesting cooperation between GR and tissue-specific factors or cofactors (17). Indeed, it has been shown that transcriptional regulators such as liver X-receptor β (LXRβ) can contribute specifically to hyperglycemia, hyperinsulinemia, and hepatic steatosis but not to the immunological system responses elicited by GC (18) and that Kruppel-like factor 15 (KLF15) selectively prevents GC-induced muscle atrophy (19). Although it has been shown that GR regulates adipocyte metabolism (12) and that GCs affect adiposity and energy expenditure both centrally (20)(21)(22) and peripherally, the detailed mechanisms underlying these metabolic changes are incompletely understood.…”
mentioning
confidence: 99%